Noninvasive preimplantation genetic testing for aneuploidy using blastocyst spent culture medium may serve as a backup of trophectoderm biopsy in conventional preimplantation genetic testing - Chen, Songchang; Wang, Li; Hu, Yuting; Yao, Yaxin; Gao, Fangfang; Chang, Chunxin; Zhang, Lanlan; Huang, Hefeng; Lu, Daru; Xu, Chenming (BMC medical genomics, 2025)
To investigate whether the noninvasive preimplantation genetic testing (niPGT) complement conventional preimplantation genetic testing (PGT) in the embryos for aneuploidy. 40 spent culture medium (SCM) samples from routine embryo culture were collected, and half of each SCM (10 µL) sample was used for whole genome amplification, while the other half was stored at -80 °C for 3-6 months. Thirty-six out of 40 fresh SCM samples were successfully amplified and sequenced. Thirty-six paired frozen-thawed SCM samples showed 100% concordance with the freshly amplified SCM samples. Then, SCM and trophectoderm (TE) samples from 149 blastocysts from 51 couples were collected. A 98.0% successful SCM sample amplification rate (146/149) was achieved. For the 146 paired TE biopsy and SCM samples, the overall concordance rate was 82.9% (121/146). Ten embryos with aneuploid TE results but euploid niPGT results were donated. A 70.0% (7/10) true negative rate was achieved by niPGT with respect to the inner cell mass (ICM) results (TE-positive embryos). These results suggested that SCM stored at -80 °C for 6 months without affecting niPGT results based on NICSInst amplification.